A better strategy: using green GDP to measure economic health - Zheng, Xinhao; Chen, Yuexin (Frontiers in Environmental Science, 2024)
Gross Domestic Product (GDP) is the most well-known and widely used measure of a country ’s economic health. However, GDP does not account for natural resources and environmental protection, leading to an incomplete picture of economic well-being. Therefore, green GDP (GGDP) should be the main indicator to measure a country ’ s economic health. This paper, building on extensive literature reviews, internationally accepted GGDP accounting methods, and scholarly research, proposes a new GGDP calculation model. This model is divided into two main components: natural resource loss and environmental pollution loss, each further divided into primary factors. These factors are condensed into 13 sub-criteria reflecting sustainable development capacity. Principal component analysis is used to identify representative factors, analyzing the relationship between these factors, GGDP, and global mean temperature. The impact of each factor on temperature projections from 2020-2040 is also examined. Utilizing the Integrated Environmental Sustainability Index (IESI), a global temperature mitigation prediction model is established, considering epidemic factors, and sea and land temperatures in different climate regions. The results indicate a 74% probability that a positive GGDP growth rate is positively correlated with temperature change over 50 years. The GGDP model reveals development patterns and differences between global GDP and green GDP, and assesses the relationship between eco-efficiency, GGDP, and global mean temperature. Both green GDP and total GDP are rising, but green GDP is growing significantly slower. The share of GDP from natural resource-dependent activities has decreased from 90% in the 1970s to 80% in 2020, highlighting the increasing gap due to reliance on natural resources. This trend suggests declining overall ecological efficiency, increasing environmental pressure, and reduced potential for sustainable development. Our analysis demonstrates that all factors are proportional to global temperature, indicating that natural resource utilization and pollution emissions significantly impact economic growth and temperature rise. Finally, we evaluate global sustainable development from economic and environmental perspectives, establishing a method for sustainable development assessment. Using Brazil as a case study, we apply the model to determine the values of each component and provide a comprehensive analysis and solutions.